New therapeutic targets for endometriosis predicted through mendelian randomization analysis and case-control trials - Zheng, Linyao; Yin, Yue; Wang, Xiaotong; Wang, Baoju; Cui, Ran; Zhang, Guangmei (Frontiers in Genetics, 2025)
IntroductionEndometriosis is a common chronic gynecological condition that affects approximately 10% of women of reproductive age worldwide.MethodsThis study utilized large-scale genome-wide association study data and explored the causal relationship between blood metabolites, plasma proteins, and endometriosis via Mendelian randomization and colocalization analysis methods. Clinical pathological data were collected, and hypotheses were validated through experiments such as ELISA, RT-qPCR, and Western blotting.ResultsRSPO3 and FLT1 were found to be potentially associated with endometriosis within the proteome. External validation and colocalization analysis confirmed the robustness of the association with RSPO3. Blood and tissue samples were collected from clinical patients to assess the accuracy of these predictions.DiscussionThese results suggest that RSPO3 may be a new target for the treatment of endometriosis, providing a direction for future drug development.